AKSI KOLABORASI PENTAHÉLIX DALAM REHABILITASI DAN PENANAMAN MANGROVE DI PULAU KAPOTA WAKATOBI, SULAWESI TENGGARA, INDONESIA: PENTAHÉLIX COLLABORATION ACTION IN THE REHABILITATION AND PLANTING OF MANGROVES ON KAPOTA ISLAND, WAKATOBI, SOUTHEAST SULAWESI, INDONESIA - Sariamin Sahari; Nasrun; Harudin; Alfi Kusuma Admadja; Normayasari; Nur Ikhsan; Muhammad Musrianton; Arham Rumpa; La Ode Mansur; Wa Ode Asma La Dia; Sunarwan Asuhadi (Jurnal Pengabdian Masyarakat Pesisir, 2026)
The degradation of mangrove ecosystems in Indonesia’s coastal areas, particularly along the shores of Kapota Island in Wakatobi, calls for a restoration approach that integrates ecological, social, and educational aspects in a comprehensive manner. This activity is a community service initiative involving mangrove rehabilitation and planting, organized as part of the Kapota Maliga Festival Kabuenga Wa Sinta on Kapota Island, Wakatobi National Park, on Thursday, April 2, 2026. The activity involved a pentahelix collaboration: academics, marine national park managers, community conservation groups, university students, and international school students. The method used was Participatory Action (PA), comprising site assessment, technical training, implementation of structured planting, cross-cultural educational exchange, and support.ng The results of the activity showed that 500 seedlings were planted across an area of 0.12 hectares, with an initial survival rate of 95%. The collaboration successfully established a community-based monitoring mechanism, improved the conservation literacy of international students, and strengthened local capacity in coastal ecosystem management. Key challenges included logistical coordination, hydrometeorological variability, and the need for long-term funding. It was concluded that the pentahelix model within the framework of a cultural festival is effective as a sustainable, participatory, and educational restoration framework. Recommendations include institutionalizing cooperation, integrating the initiative into service-learning curricula, and developing green funding schemes